2015
DOI: 10.4314/ijbcs.v8i6.30
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic des causes de complication du diabète et des méthodes de prévention à Bobo-Dioulasso, au Burkina Faso

Abstract: Au Burkina Faso, on assiste à une progression du diabète due, en grande partie, à l'ignorance, aux nouvelles et mauvaises habitudes alimentaires. L'objectif de notre étude était de diagnostiquer les causes de complications de cette maladie afin de les prévenir. Notre étude a été conduite à Bobo-Dioulasso de mars à septembre 2012. Les enquêtes et des mesures biologiques ont été réalisées sur 574 patients diabétiques. Les statistiques descriptives et les tests de corrélation ont été faits à l'aide du logiciel SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Furthermore, Saleem and Basha (2010) reported that flavonoids could inhibit the low-density lipoprotein (LDL) cholesterol oxidation and prevent atherosclerosis and decrease the cardiovascular disease risk. Since there is positive correlation between diabetes and cardiovascular disease (Koevi et al, 2014), this probably explains why the diabetes patients refer to Combretum molle and Pericopsis laxiflora. According to Ajibesin (2011), several reasons may explain the utilization of the plant materials used in the treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Saleem and Basha (2010) reported that flavonoids could inhibit the low-density lipoprotein (LDL) cholesterol oxidation and prevent atherosclerosis and decrease the cardiovascular disease risk. Since there is positive correlation between diabetes and cardiovascular disease (Koevi et al, 2014), this probably explains why the diabetes patients refer to Combretum molle and Pericopsis laxiflora. According to Ajibesin (2011), several reasons may explain the utilization of the plant materials used in the treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In Burkina Faso, as in several African countries, diabetes is becoming a very serious disease and a public concern. Recently, it was found that many people were in the risk of diabetes when they reached age 40 and 66% of diabetes patients were women (Koevi et al, 2014). Other studies showed two types of treatments people refer to.…”
Section: Introductionmentioning
confidence: 99%
“…In Burkina Faso, there is a progression of diabetes mainly due to ignorance, new and bad eating habits (Koevi et al, 2014). In 2015, prevalence rate of diabetes was 8.5% (10.4% among women and 6.9% among men) in urban areas of Ouagadougou (Millogo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, prevalence rate of diabetes was 8.5% (10.4% among women and 6.9% among men) in urban areas of Ouagadougou (Millogo et al, 2015). The prevalence is linked to factors such as obesity, poor diet, low physical activity, gender and age (Koevi et al, 2014;Millogo et al, 2015).There is complexity in the drug treatment of diabetes due to its progressive nature and association with other cardiovascular risk factors such as hypertension, obesity, smoking, stroke, kidney failure, leg amputation, vision loss and nerve damage. Modern management of disease, particularly constraining, from insulin injections (type 1 diabetes) to anti-diabetic drugs (type 2 diabetes) and requires lifelong treatment and regular follow-up (Gbekley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ce n'est donc pas une maladie unique mais plutôt un ensemble d'anomalies métaboliques et pathologiques, avec une variété de causes environnementales et héréditaires (Jansse et al, 2007). L'âge, le sexe, la profession, le revenu et l'antécédent familial représenteraient les facteurs de risques d'apparition du diabète (Koevi et al, 2014). Le diabète est l'une des maladies non transmissibles les plus répandues dans le monde, avec un effectif de patients diabétiques en 2014 qui avoisinait 422 millions de personnes (OMS, 2016).…”
Section: Introductionunclassified